2016
DOI: 10.1353/bsr.2016.0028
|View full text |Cite
|
Sign up to set email alerts
|

Black Women with Multiple Sex Partners: The Role of Sexual Agency

Abstract: Motivations of low-income substance using heterosexual Black women in New York City for having multiple sexual partners are explored in this paper. Analysis of in-depth interviews with 50 study participants demonstrates that their relationships consisted of those who had: (1) a main sex partner and a secondary sex partner; or (2) two or more “casual” partners. Individual-level motivations for extra relational sex fell into four dominant themes: sexual pleasure, partner infidelity, sex exchange and past main pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…This analysis of YBW’s experiences of gendered racism and agency illustrates the cultural context of the sexual socialization of Black women (Campos et al, 2016; Stephens & Phillips, 2005). The women in the study expressed that their attractiveness to male partners depended on cultural scripts that were hyperfeminine and sexual (Stephens & Phillips, 2005) and stereotypes were exemplified in sexual interactions with men.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This analysis of YBW’s experiences of gendered racism and agency illustrates the cultural context of the sexual socialization of Black women (Campos et al, 2016; Stephens & Phillips, 2005). The women in the study expressed that their attractiveness to male partners depended on cultural scripts that were hyperfeminine and sexual (Stephens & Phillips, 2005) and stereotypes were exemplified in sexual interactions with men.…”
Section: Discussionmentioning
confidence: 91%
“…Previous research has shown that there is a connection between internalization of negative stereotypes, low selfesteem, and engaging in risky sexual behaviors among Black women (Peterson et al, 2007;Prather et al, 2016;Thomas et al, 2004). Repeated social stigma can be internalized, and therefore challenge Black women's efforts toward fostering healthy relationships with their sex partner(s) (Campos et al, 2016;Davis & Tucker-Brown, 2013;Pahl et al, 2020). These negative social stereotypes and depictions of such stereotypes create a discourse around Black women's sexuality which normalize sexual scripts threatening sexual health decision making (Fritz et al, 2020;Townsend et al, 2010).…”
mentioning
confidence: 99%
“…One study in Jackson, MS found that women were more likely to engage in sexual concurrency if they had one or more partners with a history of incarceration [51]. One study that used a Black feminist framework analyzed qualitative data posited that some African American women may engage in concurrent sexual partnership as a form of resistance to male-dominated sexual norms within society [69]. However, although autonomy may be important for self-esteem and resilience, studies have shown low or inconsistent use of preventive selfreported HIV risk behaviors among women who engaged in those relationships, which is problematic for HIV prevention [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Another study looking at a sample of Black women found that motivations for having sex with multiple male partners or having extra-relational sexual encounters included economic advancement and stability and emotional benefits [66]. Together, the findings in this area highlight a gap in the literature of a well-rounded understanding of how Black girls and women view the activity of sex and sexual behavior and the agency they may lack in their relationships with men.…”
Section: Sexual Agency: Balancing Power Dynamics In Romantic Relation...mentioning
confidence: 96%